A thermophysical and structural characterization of ionic liquids with alkyl and perfluoroalkyl side chains - Vieira, N. S. M. (2015)
The authors thank FCT/MEC (Portugal) for financial support through grants SFRH/BD/100563/2014 (N. S. M. V.) and SFRH/BPD/94291/2013 (K. S.), FCT Investigator contracts (A. B. P., J. M. M. A., I. M. M. and J. M. S. S. E) and through projects PTDC/CTM-NAN/121274/2010, FCT-ANR/CTM-NAN/0135/2012, PTDC/EQU-FTT/118800/2010, UID/QUI/00100/2013 and UID/Multi/04551/2013. The NMR spectrometers are part of The National NMR Facility, supported by FCT/MEC (RECI/BBB-BQB/0230/2012).